Wood Anatomical Structure Could Determine Wood Quality and Its Utilization: A Hypothesis - Ratikanta Maiti (International Journal of Economic Plants)
The present paper discusses the possible role of wood anatomical structure on determination of wood or timber quality and its utility. On the basis of wood anatomy species may be classified as hard or strong wood for fabrication of strong furniture and soft wood for fire wood, fences or paper pulp. Wood fiber cell morphology determines the strength of the wood and or fabrication of paper pulp. Wood having highly thick walled lignified fiber cells could be useful for strong furniture, while the wood having broad lumen and thin cell wall are useful for fabrication of paper pulp.